Goro Gheri, secrets et secrétaires à Florence sous Laurent de Médicis, duc d’Urbin - Hélène Miesse (Laboratoire Italien)
Traditionally qualified as secretary to Laurent II, Duke of Urbino, Goro Gheri was part of the Medici’s policy to control Florence. By examining several letters from his correspondence, the article considers the tasks and responsibilities entrusted to Gheri at a critical time in the Medici rule of Florence: the years that saw it change from a Republic to a Principate. Supported by the results of the studies on the Florentine chancellery carried out by Vanna Arrighi and Francesca Klein, the analysis of the epistolary documents – the addresses and introductory formulae of which are considered to evaluate the relevance of the qualification of Gheri as secretary – allows the assessment of the status given to him by contemporaries as well as the functions and tasks given to him by the Medici. Situating Gheri in his professional setting and redefining his powers allows for an understanding of the negative judgements made about him by authors such as Francesco Guicciardini then Bernardo Segni, Benedetto Varchi and Jacopo Nardi.